The influence of budget policy on economic security and socio-economic development in the Ukraine - Zatonatska, T. G.; Stavytskyy, A.V. (Ekonomika, 2009)
The consolidation of economic security of the state, its protection against all external threats should become one of the main directions in the realization of budget expenses in short-term and in long-term prospects. According to this conception, budget expenses are to finance top-priority components of economic security.Some theoretical and methodological approaches concerning the analysis of the influence of budget instruments on parameters of economic security and socio-economic development of the country are suggested.For conducting this investigation, certain econometric models with the best functional forms have been selected and analysed. The most important instruments in budget policy such as state buying, expenses for fundamental investigations, expenses for economic development and expenses for social sphere have been considered under the condition of the Ukrainian economy. The influence of budget instruments on certain parameters that characterize the economic security of the state has been worked out in detail. As a result of the investigation, the main threats for the Ukrainian economic security have been formulated and the ways out have been proposed.The authors state that in the process of the investigation almost all budget instruments have a positive influence on the level of Ukrainian economic security, they stimulate economic development and increasing of social living standards of the population.
Keywords: economic security; econometric modelling; state expenses; investments